Antibacterial activity of biosynthesized silver nanoparticles using clinacanthus nutans extract - Waiezi, Salahaedin (2020)
Several techniques were used to produce nanoparticles due to various advantages and disadvantages. Hence, the suggested method to overcome this problem was a ‘green’ method. This study employed Clinacanthus nutans (C. nutans) extract in the synthesis of silver nanoparticles (Ag NPs) and evaluated its antibacterial potential. In this study, Ultraviolet-visible spectroscopy (UV-Vis) result revealed that the formation of the Ag NPs with an absorption peak at approximately 380 to 420 nm is an optimized condition. The synthesized Ag NPs was then characterized based on the particle size, shape and morphology using X-Ray Powder Diffraction Analysis (XRD), Energy Dispersive X-ray spectroscopy (EDX), Transmission Electron Microscopy (TEM), and Field Emission Scanning Electron Microscopy (FESEM). The XRD confirmed the crystal nature of the Ag NPs while the FESEM showed the spherical shape of the Ag NPs. FESEM and TEM indicated the range of Ag NPs size is in between 20 – 30 nm with a spherical shape. Subsequently, the antibacterial activity of the synthesized Ag NPs through Disk Diffusion Technique (DDT) indicated effective inhibition against a few bacteria including Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. In contrast, there was a nominal antibacterial activity against Enterococcus faecalis and Methicillin-resistant Staphylococcus aureus. In general, this study focuses on the potential of C. nutans in the reduction, stabilization, capping, and synthesizing the Ag NPs as an environment economic, and easy technique.